Factors Related to the Use of KB Implants at the Lalang Village Health Center, Medan Sunggal District in 2021. - Sukma Yunita (Science Midwifery, 2021)
Population growth in Indonesia is a country with the fourth largest population in the world. According to the projections of the Central Bureau of Statistics (BPS) there are many factors that influence mothers not to use implanted contraceptives, namely knowledge, IEC, husband's support, research objectives. This study uses a type of research using quantitative research. The population in this study are all women of EFA in the Lalang Village Health Center, Medan Sunggal District in 2021, as many as 54 people. The sample in this study is total sampling. Analysis of the data used Through the Chi-square test, conclusions are then drawn, if the P value <0.05 then the hypothesis is accepted. The results of the study, the knowledge factor was significantly related to the use of implants at the Lalang Village Health Center, Medan Sunggal District in 2021, with ap value = 0.026 (p < 0.05). The perception factor of children's values ​​was significantly related to the use of implants at the Lalang Village Health Center, Medan Sunggal District in 2021, with ap value = 0.005 (p <0.05). The husband's support factor was significantly related to the use of implants at the Lalang Village Health Center, Medan Sunggal District in 2021, with ap value = 0.007 (p <0.05). The KIE factor was significantly related to the use of implants at the Lalang Village Health Center, Medan Sunggal District in 2021, with ap value = 0.003 (p <0.05). The conclusion is that there are factors that have the most influence on the perception of children's values. Suggestions are expected from the results of this study to improve the midwife.